Evolutionary design for sustainability during climate change. (December 2022) - Bejan, A.; Gunes, U.
Abstract: This article reveals the thermodynamics of human sustainability on earth: (i) Production of power increases and, necessarily, the consumption of source energy increases (fuel, food, area covered by solar panels and windmills). Greater efficiency and energy conservation do not translate into less fuel consumption. (ii) Consequently, the world population will continue to increase monotonically. (iii) The power generated, consumed, and dissipated by the world population will continue to increase because every individual and group makes decisions in the direction of achieving greater wealth. The scatter in the data (the diversity) is because more advanced societies facilitate greater human movement per unit of fuel consumed. The way forward consists of making consistent steps on several paths: (a) Greater efficiency, (b) Cleaner power generation, (c) More economical distribution of power on the globe, and (d) Greater flow connectivity (empowering) of the pockets of populations that, unlike advanced societies, do not benefit from greater movement (access) per unit of fuel consumed. Any idea that moves a population toward greater movement (access) counts: increasing power plant efficiency, power & refrigeration, transportation evolution, energy in buildings, climate evolution and prediction, and reshaping the coastline. Highlights: Greater efficiency and energy conservation do not translate into less fuel consumption. The World population will continue to increase monotonically. Power generated, consumed, and dissipated by the world will continue to increase. More economical distribution of power on the globe. Greater flow connectivity (empowering) of underdeveloped pockets of populations.